Hands-on Unity 2022 game development - Borromeo, Nicolas Alejandro (Expert insight., 2022)
Unity is a cross-platform game engine that provides you with powerful but simple-to-use features to solve the most common problems in Game Development, such as rendering, animation, physics, sound, and effects. You'll learn to use these features to create simple but complete games (and all the nuances needed to handle Unity). Complete with hands-on tutorials and projects, this book will teach you to use the Unity game engine, create C# and visual scripts, integrate graphics, sound, and animations, and manipulate physics to create interesting mechanics for your game. You'll then code a simple AI agent to challenge the user and work with profiling tools to ensure code efficiency. Finally, you'll work with Unity's AR tools to create AR experiences for 3D apps and games before publishing them to the world. If you are interested in creating impressive, commercial-quality games that are playable on a variety of platforms, then you've come to the right place.